2020
DOI: 10.1007/s40263-020-00767-9
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotics and Risk of Neuroleptic Malignant Syndrome: A Population-Based Cohort and Case-Crossover Study

Abstract: Background: Neuroleptic malignant syndrome (NMS) is a rare and acute adverse drug reaction associated with antipsychotic therapy. However, few data on the risk and epidemiology of NMS are available.Objectives: To ascertain the incidence risk and all-cause mortality of NMS associated with antipsychotic use, and to assess the association of recent antipsychotic exposure and NMS.Methods: We did a population-based study using data from the Hong Kong Hospital Authority's Clinical Data Analysis and Reporting System … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…Of the 114 included articles, the case‐crossover design was the most common (100, 88%), 18–117 followed by the case‐time‐control (19, 17%), 38,63,67,71,86,118–131 and case‐case‐time‐control (4, 3%) 33,47,48,86 . (Table 1) The most common outcomes measured in these studies were hospitalization (43, 38%), cardiovascular events (22, 19%) and fall‐related injury/fracture (15, 13%).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 114 included articles, the case‐crossover design was the most common (100, 88%), 18–117 followed by the case‐time‐control (19, 17%), 38,63,67,71,86,118–131 and case‐case‐time‐control (4, 3%) 33,47,48,86 . (Table 1) The most common outcomes measured in these studies were hospitalization (43, 38%), cardiovascular events (22, 19%) and fall‐related injury/fracture (15, 13%).…”
Section: Resultsmentioning
confidence: 99%
“…However, data remain heterogenous; studies are difficult to compare ( 27 , 28 ). The relevant literature often takes substances, substance classes, or adverse effects itself as a starting point rather than diagnoses ( 3 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…NMS is a rare event, but current incidence estimates continue to vary widely, between 0.016 and 0.1% exposed persons ( 30 , 39 ). One recent study in individuals with schizophrenia or schizoaffective disorder reported incidence rates according to PY exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific evidence is controversial, as information on symptoms, prevalence, course of disease and prognosis of NMS is mainly based on individual case reports and only a few reviews. In antipsychotic users, the incidence of NMS is ~0.06–1.4% [ 15 ]. Recent studies have shown that NMS is less pronounced among SGA compared to FGA (lethality is higher: 3% for FGA vs. 16.3% for SGA) [ 16 , 17 ].…”
Section: To the Editormentioning
confidence: 99%